Check list of Slovenian Microlepidoptera - Tone Lesar; Marijan Govedič (Natura Sloveniae)
A checklist of the Microlepidoptera species recorded in Slovenia is presented. Each entry is accompanied by complete references, and remarks where appropriate. Until now, the data on Microlepidopteran fauna of Slovenia have not been compiled, with the existing information scattered in literature, museums and private collections throughout Europe. The present checklist is based on records extracted from 290 literature sources published from 1763 (Scopoli) to present. In total, 1645 species from 56 families are listed.